Knygos kultūra ir mentalitetų istoriniai tyrimai - Berenis, Vytautas (Knygotyra, 2003)
The article deals with the theoretical and practical aspects of books. The increasing interest in the book as a phenomenon of cultural and social life is related to the development of information and mass communication networks. The history of the culture of print emerged as a discipline of culture in the environment of the French Annales school and is related to the beginnings of the study of mentalities. The works by Lucien Febvre, Roger Chartier, Carlo Ginsburg and Robert Darnton broadened the field of book study and provided the framework for the analysis of the book as a factor of the level of social consciousness. The author maintains that the concept book culture introduced by Paul Raabe brought the study of book history closer to general history of culture, which encompasses the developments in sociology, literary studies, and history. Their methodological statements enable demonstrating the status of the Lithuanian society based on the various contexts of book existence: literacy (reading/writing), the ratio of religion and secularization, artistic style, forms of ideology and their development.